The components of life cycle of corporation - Шишка, Роман Богданович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2015)
The article deals with the life cycle of corporations as legal entities and their economic and legal integral part. The last one is seen by the author in internal organizational legal relationships and possibility of stipulation in the local normative acts of corporations of such rules that would prevent the crisis phenomena and internal conflicts. It is accented on two the most popular theories of life cycle of organization.